Modern concepts of skin dendritic cells - O. V. Antonova; P. N. Trofimov; V. R. Khairutdinov; I. E. Belousova; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Based on the literature review this article is about the latest data of the classification and functions of dendritic cells in healthy skin and in disease.